2019
DOI: 10.1016/j.concog.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Intentional binding coincides with explicit sense of agency

Abstract: Sense of agency, a feeling of generating actions and events by oneself, stems from action-outcome congruence. An implicit marker of sense of agency is intentional binding, which is compression of subjective temporal interval between action and outcome. We investigated relationships between intentional binding and explicit sense of agency. Participants pressed a key triggering auditory (Experiment 1) or visual outcome (Experiment 2) that occurred after variable delays. In each trial, participants rated their ag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
91
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 85 publications
(175 reference statements)
11
91
1
1
Order By: Relevance
“…Conversely, in the study by Berberian et al (2012) described before, intentional binding and control ratings were positively correlated across the levels of autonomy of the flight simulation system. Finally, a recent study by Imaizumi and Tanno (2019) examined inter-individual and intra-individual correlations between intentional binding and agency ratings while manipulating the action-outcome intervals for auditory and visual outcomes. The authors found intra-individual correlations between intentional binding and agency ratings while inter-individual correlations were observed only for the auditory outcomes.…”
Section: Relationship Between Intentional Binding and Explicit Contromentioning
confidence: 99%
“…Conversely, in the study by Berberian et al (2012) described before, intentional binding and control ratings were positively correlated across the levels of autonomy of the flight simulation system. Finally, a recent study by Imaizumi and Tanno (2019) examined inter-individual and intra-individual correlations between intentional binding and agency ratings while manipulating the action-outcome intervals for auditory and visual outcomes. The authors found intra-individual correlations between intentional binding and agency ratings while inter-individual correlations were observed only for the auditory outcomes.…”
Section: Relationship Between Intentional Binding and Explicit Contromentioning
confidence: 99%
“…Simple main effects of delay were found for both movement conditions (active: F(2, 22) = 13.37, p < .001, η 2 p = .549; passive: F(2, 22) = 17.57, p < .001, η 2 p = .615), indicating that a comparable effects of movement were also found for all delay conditions (300 ms: F(1, 23) = 44.78, p < .001, η 2 p = .661; 400 ms: F(1, 23) = 24.12, p < .001, η 2 p = .512; 500 ms: F(1, 23) = 9.62, p = .005, η 2 p = .295). However, smaller effect sizes in the larger delay conditions suggested that those intentional binding-like effects were reduced by the action-outcome temporal discrepancy violating internal prediction (Haggard et al, 2002;Imaizumi & Tanno, 2019;. This finding was supported by a follow-up ANOVA on the differential between the active and passive conditions, which showed a significant effect of delay (F(2, 46) = 3.99, p = .025, η 2 p = .148) with a significant difference between the 300-and 500-ms delay conditions suggesting a weaker intentional binding for a large delay (p = .021; no differences between the other pairs: ps > .441).…”
Section: Trial Durationmentioning
confidence: 91%
“…This model of resonant binding via simulated embodied engagements suggests patterns of neuronal synchronization could potentially be linked to either the overt or covert specific actions. As described in Safron (2019d), partially-expressed motor commands may provide a basis for not just attentional control, but also the intentional driving of working memory and action (Schurger et al, 2012;Fifel, 2018;Imaizumi and Tanno, 2019;Suzuki et al, 2019). Thus, ESMs may form cores of consciousness as dominant sources of integrated effective connectivity across the entire brain, both with respect to coherent perception and action.…”
Section: Phenomenal Binding Via Esmsmentioning
confidence: 99%